Implementation of Corporate Social Responsibility in Increasing Company Performance in the Banking Sector in 2016-2020 - Hery Haryanto; Ivana Metta Noviany (Program Sarjana Manajemen Universitas Internasional Batam, 2023)
The current era of globalization has triggered fierce competition in the business world. This competitive situation makes companies try to be the best in their sector by improving their performance, this also applies to the banking sector. A good company is a company that upholds high morality. A company can be judged on the success of its social responsibility by prioritizing moral and ethical principles, the best results can be achieved without any loss from other community groups (Suaryana, 2011). One of the strategies that companies can take to improve their performance is to implement corporate social responsibility or what is commonly known as social responsibility. Social responsibility is a basic theory where a company needs to build harmony with the community and the environment in which it operates.